Todim Method For The Selection Of The Elective Courses - Adali, Esra Aytaç; Işik, Ayşegül Tuş; Kundakci, Nilsen (European Scientific Journal, ESJ, 2016)
The selection of the elective courses considering the undergraduate students’ abilities and interests is a crucial decision. This decision also affects their academic career and job proficiency. In this paper it is aimed to guide the students for the elective course selection via TODIM (an acronym in Portuguese of Interactive and Multi Criteria Decision Making) method. TODIM method is one of the MCDM methods which is used to order the alternatives and based on pair comparisons between them. The relative measure of dominance of one alternative over another is found and finally the global values of each alternative are computed to obtain the complete ranking.